Tracking weather's flight path. - Perry, T.S.
Prototypes of systems for helping pilots and air traffic controllers cope better with untoward weather are jockeying for a place aboard critical test flights and in air traffic control and dispatch facilities on the ground. The prototypes are the products of a burst of research in technologies for detecting turbulence in all its varieties, predicting the persistence of fog, and giving pilots a clear picture of the weather ahead. They, along with systems tested last winter for detecting and predicting aircraft icing, will begin impacting commercial flights soon, although few will come into wide use before mid-decade. But all will make flying safer-and a lot more comfortable. Some 30 percent of commercial aircraft accidents have weather as a contributing factor, according to a NASA planning group. The paper discusses turbulence and its detection, the high hopes for LIDAR, tackling the problem of wakes, detection of rain, and icing factors
Keywords: LIDAR; Air traffic control; Air traffic controllers; Aircraft icing detection; Aircraft icing prediction; Dispatch facilities; Fog persistence prediction; Pilots; Rain detection; Test flights; Turbulence detection; Wakes